Identifikasi Faktor Yang Mempengaruhi Besaran Biaya Dalam Pelaksanaan Proyek Skala Kecil Di Bali - Ida Ayu Cri Vinantya Laksmi; I Wayan Jawat; I Gusti Agung Gede Nodya Dharmastika (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
The realization of the implementation of a project must be within the initial project planning stage. In the planning stage, various types of activities are carried out, starting from forming the project team, preparing the schedule, planning project resources, and preparing project cost estimates. Cost estimation activities are one of the main processes in a construction project to determine the amount of funds that must be provided for a building. Without costs, the project will not be able to be implemented even if other resource elements are met. Costs in construction projects consist of direct costs and indirect costs. Based on these 2 (two) types of costs, research needs to be carried out to determine the factors that influence the nominal amount of these types. Data analysis in this research uses the Analytical Hierarchy Process (AHP) method. The results of the research show that the order of factors that have the most influence on the two types of costs include force majeure factors, availability of labor, detailed design plans, work methods, technical specifications, distance to the place where materials/tools are purchased, location of work/project, the environment around the project, and road conditions leading to the project.